"Bad Luck Mutations": DNA Mutations Are not the Whole Answer to Understanding Cancer Risk. Issue 2 (27th June 2017) - Trosko, James E.; Carruba, Giuseppe
It has been proposed that many human cancers are generated by intrinsic mechanisms that produce "Bad Luck" mutations by the proliferation of organ-specific adult stem cells. There have been serious challenges to this interpretation, including multiple extrinsic factors thought to be correlated with mutations found in cancers associated with these exposures. While support for both interpretations provides some validity, both interpretations ignore several concepts of the multistage, multimechanism process of carcinogenesis, namely, (1) mutations can be generated by both "errors of DNA repair" and "errors of DNA replication, " during the "initiation" process of carcinogenesis; (2) "initiated" stem cells must be clonally amplified by nonmutagenic, intrinsic or extrinsic epigenetic mechanisms; (3) organ-specific stem cell numbers can be modified during in utero development, thereby altering the risk to cancer later in life; and (4) epigenetic tumor promoters are characterized by species, individual genetic-, gender-, developmental state-specificities, and threshold levels to be active; sustained and long-term exposures; and exposures in the absence of antioxidant "antipromoters." Because of the inevitability of some of the stem cells generating "initiating" mutations by either "errors of DNA repair" or "errors of DNA replication, " a tumor is formed depending on the promotion phase of carcinogenesis. While it is possible to reduce our frequencies of mutagenic "initiated" cells, one can never reduce it to zero. Because of the extended period of the promotion phase of carcinogenesis, strategies to reduce the appearance of cancers must involve the interruption of the promotion of these initiated cells.